ANALISIS SPATIAL AUTO REGRESSIVE (SAR) TERHADAP FAKTOR YANG MEMPENGARUHI KASUS DIARE DI KOTA MEDAN - Rahmadani, Artika; Husein, Ismail; Cipta, Hendra (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Diarrhea disease is categorized as the top 10 most common diseases in North Sumatra, especially Medan City. The number of diarrhea cases in each sub-district in Medan City varies, indicating a relationship between regions. This is the basis for the use of spatial models to find out how much influence variables have on the incidence of diarrhea in Medan City. The Spatial Auto regressive (SAR)  model is used to adjust the relationships that exist between a set of observations or locations. In this study, the results of SAR modeling of diarrhea cases in 21 sub-districts in Medan City compared to the OLS model produced the best model. The SAR model yielded  35.82%. The significant variable for diarrhea cases in Medan City is the number of people who do not have access to PAM water ( ).